Asymmetric Hydrophosphonylation of Aldehydes using a Cinchona–Diaminomethylenemalononitrile Organocatalyst. Issue 18 (9th December 2015) - Hirashima, Shin‐ichi; Arai, Ryoga; Nakashima, Kosuke; Kawai, Nobuaki; Kondo, Junko; Koseki, Yuji; Miura, Tsuyoshi
Abstract: For the asymmetric hydrophosphonylation of aldehydes, an efficient organocatalytic approach with a diaminomethylenemalononitrile‐based hydrogen‐bonding donor catalyst is presented. The catalyst induces high yields and excellent enantioselectivities (up to 98% yield, 96% ee ). Abstract :